Cervical Cancer Screening in Iranian Women: Healthcare Practitioner Perceptions and Views - Refaei, Mansoureh (Asian Pac J Cancer Prev, 2017)
BACKGROUND: Although regular screening for cervical cancer with the Papanicolaou test is an important element for reducing the incidence and mortality of cervical cancer, the actual screening program in Iranian women is not sufficiently comprehensive at present. The purpose of this study was to explore healthcare provider perceptions of factors affecting cervical cancer screening in Iranian women. METHODS: In this qualitative study performed from September 2015 to August 2016 in Hamadan, Iran, we conducted semi-structured in depth interviews with 14 healthcare providers selected purposefully. All interviews were recorded, transcribed and analyzed according to a conventional thematic analysis approach. MAXQDA10 software was employed for data analysis. RESULTS: Four themes were extracted from data: “Inefficient management of cervical cancer screening process, Personal and professional characteristics of health care providers, Individual barriers and facilitators, Need for health system authorities to pay attention”. CONCLUSION: Increased official attention to screening, and identifying challenges and providing strategies based on these challenges will help in achieving a successful screening program. It is necessary to attend to professional features of medical science students and increase the skills of interaction with clients in addition to academic training. Efforts should be made to increase trust in healthcare providers regarding the Pap test and receptiveness of society to this screening modality through informing the public, with encouragement through the media.